Enhanced tumor homing of pathogen-mimicking liposomes driven by R848 stimulation: A new platform for synergistic oncology therapy - Xiaobei Cheng; Pei Yu; Xiang Zhou; Jiale Zhu; Yubao Han; Chao Zhang; Lingyi Kong (Elsevier, 2022)
Although multifarious tumor-targeting modifications of nanoparticulate systems have been attempted in joint efforts by our predecessors, it remains challenging for nanomedicine to traverse physiological barriers involving blood vessels, tissues, and cell barriers to thereafter demonstrate excellent antitumor effects. To further overcome these inherent obstacles, we designed and prepared mycoplasma membrane (MM)-fused liposomes (LPs) with the goal of employing circulating neutrophils with the advantage of inflammatory cytokine-guided autonomous tumor localization to transport nanoparticles. We also utilized in vivo neutrophil activation induced by the liposomal form of the immune activator resiquimod (LPs-R848). Fused LPs preparations retained mycoplasma pathogen characteristics and achieved rapid recognition and endocytosis by activated neutrophils stimulated by LPs-R848. The enhanced neutrophil infiltration in homing of the inflammatory tumor microenvironment allowed more nanoparticles to be delivered into solid tumors. Facilitated by the formation of neutrophil extracellular traps (NETs), podophyllotoxin (POD)-loaded MM-fused LPs (MM-LPs-POD) were concomitantly released from neutrophils and subsequently engulfed by tumor cells during inflammation. MM-LPs-POD displayed superior suppression efficacy of tumor growth and lung metastasis in a 4T1 breast tumor model. Overall, such a strategy of pathogen-mimicking nanoparticles hijacking neutrophils in situ combined with enhanced neutrophil infiltration indeed elevates the potential of chemotherapeutics for tumor targeting therapy.